Testing the Applicability of the Tam on Consumers' Intention to use E-purchasing in Gaborone in the COVID-19 Era - Jaiyeoba, Olumide; Svotwa, Tendai Douglas; Roberts-Lombard , Mornay; Mafatlane, Botshabelo; Mafatlane, Gertrude (Current Aspects in Business, Economics and Finance Vol. 10, 2023)
The purpose of this study is to test the applicability of the technology acceptance model in predicting consumers' intention to use e-purchasing during the period of Covid-19 pandemic lockdown. The study applied an explanatory research design and the collection of data was secured from respondents residing in Gaborone, Botswana. In total, data were collected from 259 respondents, with the data being perceived as suitable for data analysis. SPSS 26 was used to calculate inferential statistics to measure the proposed relationships in the study. The study provides knowledge on the antecedents of behavioural intention towards e-purchasing in a developing market context. The results confirm the importance of perceived ease of use, perceived usefulness, privacy concerns and attitude on the future behavioural intention of consumers towards e-purchasing in Botswana. The study can assist businesses in better understanding the importance of securing online platforms that can be easily navigated to make a purchase, securing engagement with their consumers through online chats or chatbot engagement, managing the privacy concerns of online consumers in a professional and understanding manner and educating consumers on the value added of buying goods and services online. The study adds value to the field of marketing since the combination of factors influencing behavioural intention towards e-purchases in a developing African market context has not been extensively explored before.